Thermodynamic assessment of the PbO–V2O5 system. (December 2016) - Xie, Wei; Wang, Nai; Qiao, Zhiyu; Cao, Zhanmin
Abstract: Based on the experimental phase equilibria and thermodynamic data, a critical evaluation and thermodynamic assessment of the PbO–V2 O5 system has been performed. The liquid phase is described by the modified quasichemical model, which takes short-range ordering in liquid solution into account. All intermediate phases are treated as stoichiometric compounds. A set of self-consistent thermodynamic functions for all phases in the PbO–V2 O5 system is obtained. The available phase equilibria and thermodynamic data are reproduced well within experimental error limits. Highlights: Modified Quasichemical Model is used to describe the PbO–V2 O5 liquid phase. Discrepancies of phase equilibria and thermodynamic data in literature are evaluated. A good agreement is obtained between the calculated and experimental results.